Exploring Local Potential: The Role of Bangka Village Cultural House in Community Preservation and Empowerment - Imran, Imran; Hardiansyah, Muhammad Agus (Universitas Tanjungpura, 2024)
This research aims to analyze the planning, implementation, and results of community empowerment through Rumah Budaya Kampung Bangka in Pontianak. The urgency of this research lies in the importance of local culture preservation and community economic development in the midst of modernization. This research highlights the uniqueness of Rumah Budaya Kampung Bangka as a tourist attraction that not only preserves cultural heritage, but also empowers local communities through various programs that involve active participation. The method used in this research is observation and interviews with resource persons, including the manager of the cultural house. The results showed that this cultural house succeeded in increasing community income through the sale of handicraft and culinary products, as well as attracting visitors to learn more about Malay culture. The conclusion of this study confirms that the success of Kampung Bangka Cultural House depends on the collaboration between the government and the community, as well as the need for evaluation and innovation in work programs to ensure sustainability and cultural development in the future. This research is expected to provide insights for other cultural house managers in developing similar programs